The Morphological Changes of Staphylococcus Aureus Caused by Ethanol extracts of Cocoa Beans (Theobama Cacao) through In Vitro - Dafista Diyantika; Diana Chusna Mufida; Misnawi Misnawi (Faculty of Medicine, University of Jember, 2017)
Staphylococcus aureus (S. aureus) is positive gram bacteria which often infect humans. The use of antibiotic for therapy is the factor of resistance. S. aureus resistant towards some biotic like tetracycline, streptomycin, chloramphenicol, ampicilin, eritromisin and penicillin. The increase of the resistance demands more findings on new drugs. Ethanol extracts of cocoa beans has a block capacity towards the growth of S. aureus via in vitro. The effect of antibacterial of ethanol extracts has already been proved. However, its morphology changes on S. aureus after given ethanol extracts of cocoa beans is not found yet. This research is aimed at studying the morphological changes on S. aureus after given ethanol extracts of cocoa beans. The research design is Quasi Experimental with Posttest Only Control Group Design. The sample used is S. aureus whereas the material tests is ethanol extracts of cocoa beans in concentration of 31.2 mg/mL; 15.6 mg/mL and 7.8 mg/mL. The negative control is sterile aquades and the positive control is cephalexin suspension 4 ug/mL. The method for observing the S. aureus morphology change is scanning electronic microscope. The research result shows that there is a morphology change. Given ethanol extracts of cacao seed at 7,8 mg/mL and 15,6 mg/mL, there is enlargement of wall cell and the unity of septum. And at 31,25 mg/mL, there is protrusion at the wall cell and enlargement of wall cell.Keywords: Antimikrobial, Cacao, SEM, Staphylococcus aureus.